In Silico Modeling of Hyposalivation and Biofilm Dysbiosis in Root Caries. (August 2021) - Head, D.; Marsh, P.D.; Devine, D.A.; Tenuta, L.M.A.
Root caries progression is aggravated by hyposalivation, which can accelerate the conversion of a dental biofilm from having a symbiotic microbial relationship with the host (predominance of nonaciduric species) to a dysbiotic one (dominated by aciduric species). Using a mathematical model previously employed to investigate factors associated with biofilm dysbiosis, we systematically explored the deleterious effect of hyposalivation on the composition of the biofilm and the risk of root dentin demineralization. By varying the clearance half-times of sugar (i.e., readily fermented dietary carbohydrates), we simulated hyposalivation and investigated its effect on 1) the time that the biofilm pH spends below the minimum for dentin or enamel demineralization and 2) the conversion of the biofilm from a symbiotic to dysbiotic composition. The effect of increasing sugar clearance half-times on the time that the biofilm pH is below the threshold for demineralization was more pronounced for dentin than for enamel (e.g., increasing the clearance half-time from 2 to 6 min doubled the time that the biofilm pH was below the threshold for dentin demineralization). The effect on biofilm composition assessed at 50 d showed that the conversion from a symbiotic to a dysbiotic biofilm happened around a frequency of 6 sugar intakes per day when the clearance half-time was 2 min but only 3 sugar intakes per day when the clearance half-time was 6 min. Taken together, the results confirm the profound effect that prolonged sugar clearance has on the dynamics of dental biofilm composition and the subsequent risk of root caries. This in silico model should be applied to study how interventions that alter salivary clearance rates or modify biofilm pH can affect clinical conditions such as root caries.